Juegos recreativos y motricidad gruesa, en los niños de 3 a 4 años Escuela de Educación Básica Dr. Edison Calle Loaiza, ciudad de Loja, período 2023-2024 - Vivanco Tinoco, Jazmin Elizabeth (2024)
Gross motor skills refer to the development and control of the large muscles of the body, as well as the coordinated movement of the larger parts of the body, such as the arms, legs and trunk. Gross motor skills include aspects of crawling, walking, running, jumping, throwing, catching and climbing, which are essential for children's physical development and are the basis for more complex activities in the future. The research is focused on determining if recreational games strengthen the development of gross motor skills in children from 3 to 4 years old at the Basic Education School, Dr. Edison Calle Loaiza, city of Loja. It adopted a quantitative approach, a descriptive scope and quasi-experimental design. The methods used during its development include inductive, deductive and analytical-synthetic approaches. In order to carry out the initial and final diagnosis of motor development, the Psychomotor Development Evaluation Scale was applied to a group of 23 children. The results revealed a significant improvement in motor development, evidencing in the initial diagnosis that 70% of the children investigated were at a low level. After applying the guide of activities moving my body to grow strong and healthy, an improvement of 74% of children was noted since they were located in the good and normal level. It is crucial to recognize that the early childhood years are critical for motor development, and recreational games offer a fun and effective way to stimulate physical and cognitive growth. In addition, these games lay the foundation for an active lifestyle, encouraging healthy habits from an early age. Key words: Recreation, body movements, motor skills, leisure.